COVID-19 and Older Adults: A Call to Accelerate Geriatrics Differentiated Healthcare Services in Africa (2020)
Introduction: COVID-19 pandemic is having a global impact on healthcare system around the world. Everyone is susceptible to COVID-19, but older adults aged  60 years due to physiological changes that come with ageing and possible underlying medical disorders are more susceptible [1]. The need to ensure access to healthcare services by the elderly during this pandemic is paramount. Nonetheless, it is essential that stakeholders continue to prioritize access to healthcare services and medicines among the older adults amid the fight against this global public health, especially in Africa where little attention is paid to geriatric care. Methods: This is a descriptive recommendation abstract for countries in Africa based on tailored strategies to improve access to healthcare among the geriatric population during this pandemic and in the post-pandemic era. Discussion and key conclusion: When implementing interventions to reduce the spread of disease, such as partial or total lockdown, exceptional attention must be offered to older people. Remote consultations such as telemedicine have the potential to protect healthcare workers and older adults from unnecessary exposure to disease, while ensuring continuity in the delivery of care, and in addition, decreases resource utilization across the already stressed health-care infrastructure[2]. COVID-19 is a call to accelerate improved geriatrics differentiated healthcare services in Africa by leveraging on telemedicine and technology without necessarily exposing older adults to the risk of contracting diseases by visiting healthcare settings. During COVID-19 pandemic and post-pandemic telemedicine would have unlimited potential to provide effective, appropriate, and secure care in the context of highly transmissible disease epidemics, both for management, and for regular follow-up of chronic disease among older adults. The implementation of this technology should ensure that the future policy on telemedicine includes the end-users in the planning and implementation.